Quintessentially Un-American? Comparing Public Opinion on National Identity in English Speaking Canada and the United States - Raney, Tracey (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2010)
This paper examines national identities in Canada and the United States in 1995 and 2004, a period of considerable change in both countries. Drawing on data from the International Social Science Programme National Identity modules and on research from social psychology, the central argument forwarded is that in several respects the national identities of Canadians are becoming more similar to those of Americans over time. These similarities have often been overlooked in previous Canadian research, which tends to emphasize the differences between the two countries while downplaying their shared characteristics.